Anti-metastatic effects of aqueous extract of Helixanthera parasitica - Kriengsak Lirdprapamongkol (2018)
Metastasis, the spread of cancer in body, is a major cause of death. We have screened anti-metastatic activity of aqueous and dichloromethane extracts of several not previously studied Thai herbs, using an in vitro invasion test. This involves the in vitro invasion of HCC-S102, a hepatocellular carcinoma cell line derived from a Thai patient, through a reconstituted-basement membrane (Matrigel). The aqueous extract of a plant (Helixanthera parasitica) revealed a significant inhibitory effect on the cancer cell invasion, and showed antioxidant activity. The aqueous extract was partially purified by silica gel column chromatography, and the highest anti-metastatic activity fraction showed 83% inhibition of invasion with low cytotoxic effect. However, anti-metastatic activity was not associated with the antioxidant activity of the aqueous extract. © 2003 Elsevier Science Ireland Ltd. All rights reserved.